Spaces for democracy: Researching the social learning process - Margo Schmitt-Boshnick (Adult Education Research Conference, 1995)
Critical adult educators and a number of social theorists view social learning processes as a means of contributing to the democratization of civil society. The qualitative research project discussed in this paper examines these processes within a community development oriented women’s organization.